MANAJEMEN PUBLIC RELATIONS DALAM MENGELOLA MEDIA SOSIAL INSTAGRAM - Fika Dahlia Gilang Pratiwi, Ayub Ilfandy Imran (ArtComm, 2018)
This research is based on the lack of public understanding of the importance of information on customs and public service phenomenon through cyber or online activities. Like other public service institutions, customs offices are scattered throughout Indonesia, especially the subject of this research is Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean B Yogyakarta. The object of this research is Instagram account @. Theories and concepts used in this research are public relations concepts, cyber public relations, public services, and management functions. This research is descriptive qualitative research. The results of this study indicate that the Information and Information Services Section perform all the functions of planning, organizing, directing, and controlling management. By planning, organizing, directing and controlling uploading of photos or videos about the information or activity of the customs and excise office in a dynamic and indeterminate manner on a weekly basis and when there is new information and need to be informed to the public it will be uploaded to Instagram by packing the content that has been planned in order to attract followers to read or even attract the general public to become its new followers. Key Words: Public Relations Management, Instagram, Public Service, Cyber PR